Tetramethylpyrazine in Chinese baijiu: Presence, analysis, formation, and regulation - Shi, Xiaoshan; Zhao, Shumiao; Chen, Shenxi; Han, Xinglin; Yang, Qiang; Zhang, Long; Xia, Xian; Tu, Junming; Hu, Yuanliang (Frontiers in Nutrition, 2022)
Traditional Chinese fermented baijiu is one of the six major distilled spirits consumed worldwide. It plays an important role in people’s daily life and social interactions because of its taste, nutritional value, and various health functions. Tetramethylpyrazine (TMP), also known as ligustrazine, is not only an important compound related to the flavor of Chinese baijiu but also has special pharmacological effects. It gives the baijiu a nutty and baked aroma and provides it with important health benefits. Recently, the nutritional, drinking, and health aspects of baijiu have attracted significant attention. Therefore, the study of TMP in baijiu is an important aspect of baijiu health research. This mini novel review summarizes the formation mechanism of TMP, along with the current research progress, analytical methods used, and regulation strategies associated with TMP in Chinese baijiu in recent years.